Symbolic stationarization of dynamic equilibrium models - Fabio Canova; Kenneth Sæterhagen Paulsen (Norges Bank, 2021)
Dynamic equilibrium models are specifted to track time series with unit root-like behavior. Thus, unit roots are typically introduced and the optimality conditions adjusted. This step requires tedious algebra and often leads to algebraic mistakes, especially in models with several unit roots. We propose a symbolic algorithm that simpliftes the step of rendering non-stationary models stationary. It is easy to implement and works when trends are stochastic or deterministic, exogenous or endogenous. Three examples illustrate the mechanics and the properties of the approach. A comparison with existing methods is provided.
hdl:11250/2835495
Keywords: 330; DSGE models; unit roots; endogenous growth; symbolic computation